PENGARUH Q.S AL-MAIDAH AYAT 67 TERHADAP PERKEMBANGAN DAKWAH DI INDONESIA - SUTARNO SUTARNO; RAHMAT HIDAYAT; MUHAMMAD FEBBY IRWANSYAH; MUHAMMAD SYAIFULLAH (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This article discusses the influence of Q.S Al-Maidah verse 67 on the development of da'wah in Indonesia. This verse is often referred to as an order to the Prophet Muhammad to convey the message perfectly, without fear, despite threats or risks. In the context of da'wah in Indonesia, this verse is an inspiration for preachers to continue to convey the teachings of Islam comprehensively, despite facing social and cultural challenges. This article also elaborates on the opinions of several scholars regarding the meaning of this verse and its relevance to the development of da'wah in the modern era. Using a qualitative-descriptive approach, the article draws on contemporary literature and analyses of related hadith to understand how the message of this verse affects the dynamics of da'wah in Indonesia.